Fourier transform infrared difference spectroscopy for studying the molecular mechanism of photosynthetic water oxidation - Chu, Hsiu-An (Frontiers in Plant Science, 2013)
The photosystem II reaction center mediates the light-induced transfer of electrons from water to plastoquinone, with concomitant production of O2. Water oxidation chemistry occurs in the oxygen-evolving complex (OEC), which consists of an inorganic Mn4CaO5 cluster and its surrounding protein matrix. Light-induced Fourier transform infrared (FTIR) difference spectroscopy has been successfully used to study the molecular mechanism of photosynthetic water oxidation. This powerful technique has enabled the characterization of the dynamic structural changes in active water molecules, the Mn4CaO5 cluster, and its surrounding protein matrix during the catalytic cycle. This mini-review presents an overview of recent important progress in FTIR studies of the OEC and implications for revealing the molecular mechanism of photosynthetic water oxidation.